Kajian sifat asfalt-lateks - Riza Atiq O.K. Rahmat,; Arniruddin Ismail,; Yeong , Tuck Wai (1998)
In a hot climate, asphalt pavement will age harden faster and require substantial maintenance. Age hardening causes asphalt to be stiff and brittle. The pavement layer then becomes too hard and lose its flexibility. As a result the pavement will crack and break up. In this study natural latex is added to asphalt in order to retard age hardening. The following tests were carried out on the latex-modified asphalt: penetration, softening point, absolute viscosity and kinematic viscosity. Latexmodified asphalt with latex content of 3% and 6% by weight of mix produce different properties to justify their uses in different conditions. Six percent latex content was found to be the optimum content in retarding ageing process of asphalt as well as improving its stability. However the asphalt becomes less workable. Asphalt with three percent latex content is found to be good in workability and at the same time retain the ageing process as well as improving the stability of the asphalt